Struggling With Business Corporate Cynical Impression? Powerful Methods of CSR to Enhance Corporate Image and Consumer Purchase Intention - Avotra, Andrianarivo Andriandafiarisoa Ralison Ny; Chengang, Ye; Wei, Xu; Ming, Jiang; Marcelline, Tsimisaraka Raymondo Sandra (Frontiers in Public Health, 2021)
This study focuses on the perception of Chinese students about the image of the company and their purchase intention if the organization has a business cynical impression in the minds of its targeted customers. The study proposed three different types of corporate social responsibility (CSR) to cope up with the organizational cynical impression. These types are Economic and Legal CSR, Philanthropic CSR, and Ethical CSR. The main objective of this study is to determine which CSR type is better to reduce the corporate cynical impression on corporate image and the purchase intentions of consumers. In the study design, the bootstrap approach and AMOS 24 were employed to deal with mediation. The researchers recruited 500 individuals from different educational institutions in China using a simple random selection process. The outcomes of this study indicated that all three types of CSR are successful in mitigating the detrimental effects of corporate cynicism on the image of a firm and the purchase intentions of consumers. A more effective technique of boosting the corporate image of a company and purchase intention of a consumer is via charitable CSR, which may help restore the image of a company and the purchase intention of a consumer that has been affected by corporate cynicism among its target customers.